The concept of interethnic security of the region (on the example of Tatarstan) - Rezida R. Khusnutdinova; Il’dar M. Yusupov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
When there is a social and economic disadvantage in the region, the consciousness of the subject begins to look for the image of the enemy, which more often focuses on representatives of national diasporas. Interethnic tensions are growing. The distance between ethnophores and ethnoses increases to complete mutual rejection in their area. In an aggravated situation, social security. The paper puts forward the concept of interethnic security based on minimizing threats perceived by the ethnos as a problem. An indicator of unstable security is an increase intension. Subjectively, security is expressed in the absence of fear of external threats [1]. Its predictors include: numerical and status imbalance of ethnic groups; their hyperidentificity; unemployment of the population; its low education; intolerance. The listed socio-psychological constructs are observed visually and recorded by the corresponding markers of individual and mass behavior. The purpose of theoretical and empirical research is to distinguish between manifestations of anomalies of ethnic identity and to resist extremist actions provoking interethnic and interfaith conflicts. An empirical study of the interethnic distancing of three peoples Russians, Tatars and Chuvash who make up 96 % of the region's population was conducted. The representative sample included 946 people. Based on an array of empirical data, general and individual estimated ranges of ethnic groups' distance were calculated. Predictors of increasing interethnic tension in the region they make up a structural pentabasis. Exceeding the acceptable for an ethnic group norms of any of them causes alatent murmur of ethnophores. Exceeding the norms of the two signals about the increase in protest. In case of three or more in any combination mass disobedience is possible, threatening security.